Changes of Marginal Bone Level in Patients with "Progressive Bone Loss" at Brånemark System® Implants: A Radiographic Follow‐Up Study over an Average of 9 Years. (31st October 2013) - Jemt, Torsten; Sundén Pikner, Solweig; Gröndahl, Kerstin
Abstract Background Patients have in many studies been identified with progressive bone loss and peri‐implantitis problems, but few studies are available where these groups of patients have been followed up. Purpose The purpose of this paper is to study further progression of bone loss in a cohort of 182 patients that have been reported to suffer from "progressive" bone loss and peri‐implantitis. Materials and Methods Altogether, 182 patients that have earlier been identified to suffer from "progressive" bone loss formed the present study group. Data from patients' files have been retrieved, and intraoral radiographs have been analyzed for further bone level changes. Bone loss has been measured from time of inclusion into the present group to last available radiographs. Within each patient, one or several implants were diagnosed to suffer from "progressive" bone loss (affected), whereas others are not (unaffected). Results Altogether, 145 patients (80%) were radiographically followed up on an average of 9.1 years (SD 3.77) after inclusion. Twenty‐four implants (3.1%) were lost in 16 patients (11%). Marginal bone loss was on an average 0.3 mm (SD 0.75) at stable implants with only small differences between "affected" and "unaffected" implants. In total, 67 implants (8.6%) presented an annual bone loss of >0.2 mm. Oral hygienist treatment and/or peri‐implantitis surgery did not neither reduce implant failure rate nor marginal bone loss in 88 treated patients as compared with untreated patients. Conclusions Less than one‐third of the patients identified with "progressive bone loss" showed one or more implants as failures or with high annual bone loss (>0.2 mm) during follow‐up (11.6% of implants). Treated patients (oral hygienist and/or surgery) did not perform better than untreated patients with regard to bone loss or implant failure.